Challenges, Strategies, and Islamic Ways for Effective Indonesian Economic Digitalization in the Post Covid-19 Pandemic - Siti Aminah Caniago; Denny Mustoko; Bagaskara Sagita Wijaya (Jurnal Hikmatuna, 2021)
This study aimed to describe the condition of the digital economy in Indonesia before the COVID-19 pandemic, analyze the challenges, strategies, and Islamic ways to strengthen economic digitalization in Indonesia, and describe the upgrading steps to realize economic digitalization in Indonesia. Using qualitative data and qualitative-descriptive analysis methods, the researchers analyzed the digital economy, community index, and social and economic processes. System observations and online transaction recapitulation, online journals, books, papers, and other publications were used to obtain the data of this study. As a result of this study, the challenges of economic digitalization in Indonesia are the ability of Indonesians to adapt to new technologies and the diverse locality values in Indonesia, which are still general. The strategy that can be implemented is developing end-user policies, such as end-to-end business cycle policies, and strengthening digital economy development governance that retains the value of Indonesian locality while involving various parties through collaborative steps. Besides, developing Islamic financial technologies is also required. This aims to improve sharia-compliant online market liquidity and social finance (zakÄt, infÄq, and waqf). In conclusion, the digital economy in Indonesia must encompass enhancing company processes through technology innovation, encouraging growth through government regulations, and involving new actors.